The Effects of Ceo Traits, Managerial Ownership, and Profitability on ESG Performance in Companies Listed on the Indonesia Stock Exchange - Nicholas, Jayson; Sari, Maylia Pramono (Pusat P2M Politeknik Negeri Batam, 2026)
This investigation is to look at how CEO Traits, Managerial Ownership, and Profitability affect ESG performance in manufacturing firms listed between 2021 until 2024 on the Indonesia Stock Exchange (IDX). ESG performance is an important indicator in describing corporate sustainability, as it reflects the company's commitment not only to financial aspects but also to environmental, social, and governance responsibilities. Although attention to ESG is increasing, empirical findings on internal factors that influence ESG performance still show inconsistent results, creating a research gap, especially in the manufacturing sector, which has high risks related to environmental and social issues. Pecking order theory and agency theory are pertinent theories In this study, panel data regression is utilized quantitative methodology. There are 39 manufacturing enterprises in the sample, totaling 142 observations after data cleaning. ESG performance is measured using the Refinitiv ESG score, while CEO Traits, Managerial Ownership, and Profitability are used as independent variables using firm size as variable control. The best model used is the Random Effects Model (REM) based on the results of the Chow and Hausman tests. The findings demonstrate profitability has a significant negative effect on ESG performance. This finding demonstrates that companies with shows that businesses with high profitability typically concentrate on cost efficiency and short-term profit achievement, thereby reducing the allocation of funds for sustainability activities. Meanwhile, CEO Traits and Managerial Ownership do not have an important impact on ESG Performance, suggesting that leadership characteristics and the level of share ownership by managers are not the main determinants in improving the ESG performance of manufacturing firms Indonesia. This study expands the ESG study by simultaneously testing CEO Traits, Managerial Ownership, and Profitability while considering company size. Additional investigation is advised to broaden the context of the sector or industrial region, as well as to use other factors that may influence ESG.